Identitas Komunitas Islam di Wilayah Perbatasan Indonesia-Filipina - Taufani, Taufani; Kadengkan, Dighfar; Tarmun, Alfat (Program Studi Sosiologi Agama Fakultas Ushuluddin, Adab dan Dakwah IAIN Manado, 2024)
The Indonesia-Philippines border region is a unique region due to the ethnic, cultural, and religious diversity that coexists. Islam plays a significant role as a collective identity that unites Muslim communities on both sides of the border, as well as being the foundation of values ​​in social, cultural, and economic life. This study aims to explore the dynamics of Muslim community life in the border region, focusing on social, cultural, educational, and political aspects, and how Islam functions as a social glue and symbol of collective identity. Through a qualitative descriptive approach, this study reveals that Islam is not only a spiritual guide but also a foundation of solidarity that strengthens cross-border relations. Religious traditions such as the Prophet's Birthday and joint prayers, as well as the acculturation of Islamic values ​​with local culture, create a unique social harmony. However, the community in this region also faces challenges, including the influence of modernization, social conflict, and marginalization of development. The results of the study show that Islamic identity in the border region is not only able to strengthen social cohesion, but also helps the community face the challenges of globalization without losing local traditions. In conclusion, Islam as a collective identity plays a strategic role in creating harmony and stability in the Indonesia-Philippines border region, although it requires more attention from various parties to maintain its sustainability.